Chronic Kidney Disease in Lithuanian Children: Single Center Experience - Rukšėnaitė, Ugnė; Ažukaitis, Karolis; Čerkauskienė, Rimantė; Ruzgienė, Dovilė; Vitkevič, Renata; Litvinenko, Darija; Jankauskienė, Augustina (Acta medica Lituanica, 2026)
Background: Chronic Kidney Disease (CKD) in children is relatively rare but carries high burden due to increased morbidity and mortality rates. Unlike adults, where CKD is often secondary to other conditions, pediatric CKD is primarily caused by Congenital Anomalies of the Kidney and Urinary Tract (CAKUT). In Lithuania, data on pediatric CKD are limited, and center-specific patient characteristics and management practices remain underreported in real life settings. This study aimed to assess the current patterns of pediatric CKD in a major Lithuanian tertiary center and evaluate how current practice aligns with guideline recommendations. Material and Methods: A cross-sectional study of children (<18 years) with CKD stages 2–5 at Vilnius University Hospital Santaros Klinikos Pediatric Center was conducted. CKD stages were defined according to the Kidney Disease: Improving Global Outcomes (KDIGO) 2024 guidelines, and the patients were categorized into seven groups according to CKD etiology. Anthropometric measurements, complications, comorbidities, and ongoing treatments were analyzed. Results: A total of 65 children were included (mean age 11.1 years; male-to-female ratio 1.7:1). CAKUT was the most common etiology of CKD (61.5%), with renal hypoplasia being the predominant variant, followed by cystic kidney diseases (13.9%), glomerulopathies (9.2%), and other or unknown causes (9.2%). The mean estimated glomerular filtration rate (eGFR) was 60.5 mL/min/1.73 m², and most children were in CKD stage 2 (66.2%). Differences in age, sex, eGFR, and the CKD stage across the etiology groups were not statistically significant (all p >0.05). Normal weight remained the predominant category at every CKD stage, with a prevalence of 60.0–66.7%. Nearly half of the patients had CKD-related complications, most commonly CKD-mineral and bone disorder, proteinuria, and arterial hypertension. Most children (76.9%) had received at least one treatment for CKD-related complications. Conclusions: Pediatric CKD in Lithuania remains predominantly caused by CAKUT, with most children diagnosed with CKD stage 2. Complications occur even in early stages, and the body mass index distribution does not vary significantly across the CKD stages. Management generally aligned with KDIGO guidelines, but gaps in treating proteinuria, anemia, and growth impairment remain.